Determinan Audit Report Lag dan Spesialisasi Auditor sebagai Moderasi Pada Sektor Perdagangan, Jasa, dan Investasi - Priyani, Risma Elsa; Badjuri, Achmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Audit Report Lag is the length of audit completion time measured from the closing date of the financial year as of December 31 until the publication of the independent auditor's report. This study examines the determinants of audit report lag and auditor specialization as moderating trade, service, and investment sectors listed on the Indonesia Stock Exchange in 2018 – 2020. Using the purposive sampling method, determining research samples is a sampling technique with specific criteria obtained as many as 361 company samples. The research data analysis method used the moderated regression analysis test with SPSS version 26 application. The results showed that audit opinion and the size of the public accounting firm had a significant adverse effect on audit report lag, and audit tenure had a significant positive effect on audit report lag. In contrast, the complexity of the company's operations did not affect audit report lag. In this study, auditor specialization does not moderate the relationship between audit opinion, the complexity of company operations, and audit tenure on audit report lag. Meanwhile, auditor specialization moderates the relationship between public accounting firm size and audit report lag.